Efeitos hemodinâmicos da pressão positiva contínua nas vias aéreas avaliados pelo ecodopplercardiograma - Vinhal, Gabrielle Silva (2015)
Although the use of continuous positive airway pressure (CPAP) has increased considerably, there have been few studies of its hemodynamic effects in patients with healthy cardiopulmonary systems. Objective: To evaluate the hemodynamic effects exerted by different levels of continuous positive airway pressure in healthy individuals using Doppler echocardiography. Methods: This study included 19 healthy volunteers. Three levels of continuous positive airway pressure (5, 10 and 15 cm H2O) were randomly applied for 5 minutes each; 5 minutes of rest were allowed between each application. Echocardiographic variables, vital signs and ventilation were each recorded at baseline and following each pressure application. Results: Continuous positive airway pressures of 10 and 15 cm H2O generated a reduction in the pulmonary velocity-time integral (p=0.01), as well as a reduction in right atrial area (p=0.00). Both cardiac output and heart rate were significantly decreased with each pressure setting (p=0.00 and p=0.00, respectively), whereas stroke volume and blood pressure did not change significantly. Positive correlations were observed between the mitral, pulmonary and aortic velocity-time integrals and both stroke volume and cardiac output. Conclusion: Continuous positive airway pressures of 10 and 15 cm H2O generated reductions in right ventricular preload without changing either left ventricular preload or left ventricular afterload. There was also a decrease in cardiac output due to a reduction in heart rate. A strong correlation was observed between the mitral velocity-time integral and both stroke volume and cardiac output.